Prevalence of self-reported food allergies among the Saudi population and investigation of the challenges faced by people with food allergy: A cross sectional online survey-based study - Zaher, Sara; Bookari, Khlood; Arrish, Jamila; Alnafisah, Ruyuf; alobaid, Rawan; Albuayjan, Norah; Binammar, Albandari; Alsayegh, Abdulrahman; A. Abduljawad, Eman; A. Halawani, Reham; M Alkhalaf, Majid; Al-Otaibi, Hala (Progress in Nutrition, 2023)
Background: The topic of food allergy (FA) is widely studied and investigated in developed countries. However, there are lack of published reports concerning FA prevalence in the middle-east region including Saudi Arabia (KSA). Therefore, we aimed to assess the prevalence of FA among children and adults in KSA and to identify the most common types of FAs. Methodology: An online survey was distributed to collect information about the prevalence of self-reported FA, type of FA and challenges faced by food allergic people. Results: We received 15142 responses of those 3237(21%) subjects were diagnosed with FA or taking care of someone with FA. About 15% of food allergic subjects were ≥18 years and 6.4% were <18 years. Egg was the most reported allergenic foods among our cohort for both age groups, followed by peanut and milk among the younger group and crustacean and wheat in the group ≥18 years of age. About 22% of the participants in the group ≥18 years of age have experienced food anaphylaxis at least once in the past 12 months. While 15% of the younger group had food anaphylaxis at least once in the last year. Subject’s characteristics such as age, income has shown to influence the odds of experiencing food anaphylaxis. Conclusion: The current study recorded a relatively high prevalence of self-reported FA in KSA. It also highlighted some of the challenges faced by Participants with food allergies such as lack of proper meal options for their allergic condition in restaurantsand unclarity of allergenic food in the menus. These findings shed light on the need to implement policies in favour of people with FA such as allergen labelling in restaurant’s menus and food delivery platforms.